2007
DOI: 10.1007/s11434-007-0217-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid growth cost in “all-fish” growth hormone gene transgenic carp: Reduced critical swimming speed

Abstract: Evidence has accumulated that there is a trade-off between benefits and costs associated with rapid growth. A trade-off between growth rates and critical swimming speed (U crit ) had been also reported to be common in teleost fish. We hypothesize that growth acceleration in the F 3 generation of "all-fish" growth hormone gene (GH) transgenic common carp (Cyprinus carpio L.) would reduce the swimming abilities. Growth and swimming performance between transgenic fish and non-transgenic controls were compared. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 41 publications
1
37
0
2
Order By: Relevance
“…This construct contains the recombinant sequence of the grass carp Ctenopharyngodon idellus (Cuvier & Valenciennes) growth hormone gene driven by a common carp β-actin gene promoter (Wang et al, 2001). F 5 'all-fish' GH transgenic carp used in the present study were produced on April 25, 2007, from crosses between a wild-type female and a F 4 'all-fish' GH transgenic male of a fast-growing transgenic strain as reported in previous studies (Fu et al, 2007a;Li et al, 2007). A batch of nontransgenic controls was also produced on the same day.…”
Section: Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…This construct contains the recombinant sequence of the grass carp Ctenopharyngodon idellus (Cuvier & Valenciennes) growth hormone gene driven by a common carp β-actin gene promoter (Wang et al, 2001). F 5 'all-fish' GH transgenic carp used in the present study were produced on April 25, 2007, from crosses between a wild-type female and a F 4 'all-fish' GH transgenic male of a fast-growing transgenic strain as reported in previous studies (Fu et al, 2007a;Li et al, 2007). A batch of nontransgenic controls was also produced on the same day.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Many countries are discussing or developing safety assessment strategies for fast-growing transgenic fish, and growth hormone (GH) transgenic fish are near the point of widespread commercial use (Niiler, 2000;Fu et al, 2005;Hu et al, 2007). Many studies have shown that in addition to enhancing growth rates, transgenic fish overexpressing GH can show a broad range of pleiotropic effects on morphology, physiology, metabolism, immunology and behavior (Fu et al, 1998(Fu et al, , 2007aDevlin et al, 2004Devlin et al, , 2006Wang et al, 2006;Li et al, 2007Li et al, , 2009Guan et al, 2008). Transgenic fish can be a useful model for examining the effects of GH on many physiological processes (Devlin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest swimming speed of any fish species determines their ability to survive in a natural environment [28]. Some work has indicated that GH-transgenic common carp and salmon juveniles are inferior swimmers with significantly decreased critical swimming speeds compared with control fish of the same size [29,30]. This may affect the ability of the transgenics to escape under the threat of predators.…”
Section: Viability Of Transgenic Fishmentioning
confidence: 99%
“…Several pleiotropic effects of transgenic GH genes have been reported in fish, such as changing the non-specific immune functions (Wang et al, 2006b), impairing swimming ability (Farrell et al, 1997;Li et al, 2007), skeletal abnormalities (Ostenfeld et al, 1998), and regulating sea water adaptability (Seddiki et al, 1996). Accordingly, the fitness and adaptability of transgenic fish must be carefully predicted before introduction to a natural ecosystem in order to conserve ecological balance and minimize potential ecological risk.…”
Section: Introductionmentioning
confidence: 99%